Identification of genes and proteins involved in the regulation of orchid mycorrhiza - Valadares, Rafael Borges da Silva (2014)
Orchids are characterized by producing minute endosperm-lacking seeds, which depend on mycorrhizal fungi for germination and embryo development. Some aclorophyllous orchids remain dependent on the mycorrhizal association for carbon acquisition during their whole life history, whereasother orchids develop photosynthesis. Despite the biological significance of orchid mycorrhiza, gene expression studies are lacking. We have used different highthroughput approaches in order to understanding the mechanisms regulating orchid mycorrhiza development and functioning. Firstly, we have used a 2D-LC-MS/MS approach coupled to isobaric tagging for relative and absolute quantification (iTRAQ) to identify proteins with differential accumulation in Oncidium sphacelatum at different stages of mycorrhizal protocorm development (achlorophyllous and green protocorms) after seed inoculation with a Ceratobasidium sp. isolate. Quantitative analysis showed that the expected changes in carbon metabolism in green protocorms were accompanied by enhanced accumulation of proteins involved in the modulation of reactive oxygen species homeostasis, defense related responses, phytoalexins and carotenoid biosynthesis, suggesting that orchid protocorms undergo profound metabolic changes during the switch from the fully mycoheterotrophic to the photosynthethic stage. Secondly, three different proteomic techniques were carried out in independent experiments aiming to identify changes in protein accumulation in mycorrhizal roots of the terrestrial orchid Oeceoclades maculata.Finally, O. maculatamycorrhizal roots were used for transcriptome analyses. The data revealed a strong increase in general stress responses, accompanied by changes in signaling pathways possibly related to fungal recognition and establishment of a compatible interaction. Some of the upregulated genes may be involved in the reorganization of cell structure, likely related to accommodation of the fungal symbiont in the plant roots. We have also observed in mycorrhizal roots up-regulation of genes involved in carbon metabolism, including glycolysis/gluconeogenesis and amino sugars metabolism, as well as genes involved innitrogen assimilation. The down-regulation of genes involved in the jasmonate and ABA transduction pathways, and key genes encoding anti-fungal proteins, such as chitinase and a mannose-specific binding lectin, strongly suggests an alleviation of plant defense responses in O. maculata mycorrhizal roots. In general, our data suggest that the physiology of an orchid mycorrhiza is more similar to a compatible interaction than to an arm-race between plant and fungi. Overall orchid mycorrhiza have proved to be a promising model for investigating plantfungal interactions and further studies should now address the specific roles of the genes showing differential regulation in this study.